SERVICE RESPONSIVENESS OF THE DIAGNOSTIC IMAGING DEPARTMENT AT THE NATIONAL HOSPITAL OF ENDOCRINOLOGY IN 2026 AND ASSOCIATED INFLUENCING FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the service responsiveness of the Diagnostic Imaging Department at the National Hospital of Endocrinology in 2026 and several influencing factors.Methods: A cross-sectional descriptive study combining qualitative and quantitative analyses to assess the service responsiveness of the Diagnostic Imaging Department at the National Hospital of Endocrinology.Results: The responsiveness of diagnostic imaging services of the Diagnostic Imaging Department at the National Hospital of Endocrinology in 2026 was high, with an overall responsiveness rate of 94.8% and a mean service quality score of 4.36/5. Among the evaluated dimensions, positive ratings were reported for service provision (86.4%), service quality responsiveness (88.8%), patient needs fulfillment (88.1%), and facilities and environmental conditions (90.8%). Several factors were found to be associated with the responsiveness of diagnostic imaging service quality, including patients’ length of hospital stay, infrastructure and medical equipment, human resources, examination procedures and departmental management, patient-related and external environmental factors, as well as financial conditions and healthcare payment mechanisms. These findings highlight the importance of strengthening organizational management, improving infrastructure and workforce capacity, and optimizing service processes to enhance the quality and responsiveness of diagnostic imaging services.Conclusion: The proportion of respondents rating the responsiveness of diagnostic imaging services as good of the Diagnostic Imaging Department at the National Hospital of Endocrinology in 2026 was relatively high (94.8%) compared with other departments in the hospital, with a mean score of 4.36 out of 5 points.
Keywords: Service responsiveness, diagnostic imaging, National Hospital of Endocrinology.